Study of efficacy and safety of drug eluting stent versus bare metal stent in ST elevation MI - Bakhtar, Vijay P.; Bakhtar, Niyati V.; Chaudhari, Sameer P. (International Journal of Research in Medical Sciences, 2019)
Background: The present study was conducted with the aim of determining whether drug-elutingstents are superior to uncoated stents in the setting of primaryPCI in terms of occurrence of serious adverse cardiac events. Methods: In this prospective, single blind, randomized study, 20 to 80 years old patients with acute myocardial infarction with ST-segment elevation with >30 minutes of chest pain and at least 1 mm of ST-segment elevation in at least two standard leads or a new LBBB or 2 mm of ST-segment elevation in at least two contiguous leads were included. Patients were randomly assigned to receive either drug eluting stent (DES) (Everolimus Eluting stent, Endevour-Medtronics) or bare metal stent (BMS, Cordis-Dx sonic) in a 1:1 ratio. During follow ups at 30 days and 12 months, all serious adverse cardiac events like death from cardiac or non-cardiac cause, recurrent MI, revascularization of target vessel, coronary artery bypass grafting (CABG) or other intervention to target or non-target vessel etc. were recorded and compared between groups. Results: No significant differences were found between the two treatmentgroups for occurrence of adverse events during first 30 days after the intervention. At one year follow-up, trends were observed in favorof the DES group, none of the differences weresignificant. Conclusions: No significant benefit was observed with the use of Everolimus-eluting stents in primaryPCI for acute myocardial infarction with ST-segment elevation,in comparison with baremetal stents.